Islamic Corporate Governance and Internal Control Influance on Fraud in Sharia Commercial Banks - Mariyam Chairunisa (Universitas Mercu Buana, 2020)
This study aims to examine impact of Islamic Corporate Governance and Internal Control on Fraud on sharia Commercial Bank in Indonesia. The unit analysis of this research is Sharia Commercial Banks in Indonesia which have been registered in the Financial Services Authority (OJK) period 2012 to 2017. This research was done to 11 Islamic commercial banks by using quantitative-descriptive approach. The results of this research showed that Sharia Supervisory Board and Internal Control have negative effect and unsignificant on Fraud. However, Audit Committee has a positive effect and significant on fraud .